Phrasing Techniques for Multi-Stroke Selection Gestures - Hinckley, Ken; Guimbretiere, Francois; Agrawala, Maneesh; Apitz, Georg; Chen, Nicholas (GI '06 Proceedings of Graphics Interface 2006, 2006)
Pen gesture interfaces have difficulty supporting arbitrary multiple-stroke selections because lifting the pen introduces ambiguity as to whether the next stroke should add to the existing selection, or begin a new one. We explore and evaluate techniques that use a non-preferred-hand button or touchpad to phrase together one or more independent pen strokes into a unitary multistroke gesture. We then illustrate how such phrasing techniques can support multiple-stroke selection gestures with tapping, crossing, lassoing, disjoint selection, circles of exclusion, selection decorations, and implicit grouping operations. These capabilities extend the expressiveness of pen gesture interfaces and suggest new directions for multiple-stroke pen input techniques.